Who was Jules Verne? - Buckley, James, Jr., 1963-; Copeland, Gregory (New York : Grosset & Dunlap, an imprint of Penguin Random House, 2016)
Looks at the life of nineteenth-century French novelist Jules Verne.
Includes bibliographical references (p. 106).
3-6
3-6
Keywords: Verne, Jules, -- 1828-1905 -- Juvenile literature; Verne, Jules, -- 1828-1905.; Verne, Jules, -- 1828-1905.; Authors, French -- 19th century -- Biography -- Juvenile literature; Authors, French; French authors -- Biography; Biographies